2018
DOI: 10.1038/s41598-018-33017-6
|View full text |Cite
|
Sign up to set email alerts
|

Human neural stem cell transplantation improves cognition in a murine model of Alzheimer’s disease

Abstract: Stem cell transplantation offers a potentially transformative approach to treating neurodegenerative disorders. The safety of cellular therapies is established in multiple clinical trials, including our own in amyotrophic lateral sclerosis. To initiate similar trials in Alzheimer’s disease, efficacious cell lines must be identified. Here, we completed a preclinical proof-of-concept study in the APP/PS1 murine model of Alzheimer’s disease. Human neural stem cell transplantation targeted to the fimbria fornix si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 54 publications
6
80
0
2
Order By: Relevance
“…This was not mentioned in the 3xTg and Tg2576 models. Conversely, another study showed that NSC transplantation has no effect on synaptic density, but that it does improve behaviour [54]. An opposite long-term result in transplanting hNSC into RAG-5xfAD were obtain from two studies.…”
Section: Mechanisms Of Behavioral Improvement With Different Nsc Sourmentioning
confidence: 99%
See 3 more Smart Citations
“…This was not mentioned in the 3xTg and Tg2576 models. Conversely, another study showed that NSC transplantation has no effect on synaptic density, but that it does improve behaviour [54]. An opposite long-term result in transplanting hNSC into RAG-5xfAD were obtain from two studies.…”
Section: Mechanisms Of Behavioral Improvement With Different Nsc Sourmentioning
confidence: 99%
“…In 2018, a study by McGinley suggested that transplanted hNSCs regulate microglial activation and thus reduces Aβ levels. Furthermore, the beneficial effect of the treatment on behaviour lasted for 4 months after transplantation [54] (Table 3).…”
Section: Human-derived Vs Mouse-derived Nscs In Tg2576mentioning
confidence: 99%
See 2 more Smart Citations
“…Stem cell-based therapies are defined as any treatment for a disease or a medical condition that fundamentally involves the use of any type of viable human stem cells including ESCs, iPSCs, and adult stem cells for autologous and allogeneic therapies. Emerging evidence of stem cell-based therapeutic effects from preclinical and clinical studies suggest that regenerative strategies may one day become a treatment for a wide range of vexing diseases [ 46 , 47 , 48 , 49 ]. The current progress of therapies using various stem cells such as MSCs (e.g., ADSCs and BM-MSCs), urine-derived stem cells, iPSCs, and spermatogonial stem cells (SSCs) are described and discussed in this Special Issue.…”
Section: Stem Cell-based Therapymentioning
confidence: 99%